Synthesis of pentasubstituted 2-aryl pyrroles from boryl and stannyl alkynes via one-pot sequential Ti-catalyzed [2 + 2 + 1] pyrrole synthesis/cross coupling reactions. Issue 37 (15th September 2020) - Cheng, Yukun; Klein, Channing K.; Tonks, Ian A.
Abstract : Multisubstituted pyrroles are commonly found in many bioactive small molecule scaffolds, yet the synthesis of highly-substituted pyrrole cores remains challenging. Abstract : Multisubstituted pyrroles are commonly found in many bioactive small molecule scaffolds, yet the synthesis of highly-substituted pyrrole cores remains challenging. Herein, we report an efficient catalytic synthesis of 2-heteroatom-substituted (9-BBN or SnR3 ) pyrroles via Ti-catalyzed [2 + 2 + 1] heterocoupling of heteroatom-substituted alkynes. In particular, the 9-BBN-alkyne coupling reactions were found to be very sensitive to Lewis basic ligands in the reaction: exchange of pyridine ligands from Ti to B inhibited catalysis, as evidenced by in situ 11 B NMR studies. The resulting 2-boryl substituted pyrroles can then be used in Suzuki reactions in a one-pot sequential fashion, resulting in pentasubstituted 2-aryl pyrroles that are inaccessible via previous [2 + 2 + 1] heterocoupling strategies. This reaction provides a complementary approach to previous [2 + 2 + 1] heterocouplings of TMS-substituted alkynes, which could be further functionalized via electrophilic aromatic substitution.